Tinjauan Yuridis Pelaksanaan Review Hasil Pemilihan Penyedia dalam Pengadaan Barang atau Jasa oleh Pejabat Pembuat Komitmen - Ersanda, Elsha; Rustan, Ahmad; Irwansyah, Irwansyah; Umar, Wahyudi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The role of the Commitment Making Officer (PPK) is very important to ensure procurement objectives are achieved by reviewing the results of the selection of government procurement of goods and services so that the entire procurement process is carried out transparently, fairly and in accordance with applicable regulations. This research aims to analyze whether the process of reviewing election results in procurement process No. 15117081 carried out by PPK Southeast Sulawesi has complied with the principles of transparency, accountability and fairness in selecting tender winners based on LKPP Regulation No. 12 of 2021. The research method used is a legal research method with a statutory approach and case study. The results of the research show that the implementation of the review by the PPK in the aquo case is not in accordance with the provisions of LKPP regulation No.12 of 2021. The review should be carried out by the PKK only based on the Minutes of Election Results (BAHP) documents received, not providing field evidence or clarification to participants or other parties. The implication of these findings is that there is a potential violation of the principles of government procurement of goods and services which must be carried out transparently, fairly and in accordance with regulations.